Number 53 (December 2011) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2011)
(December 2011) - Population Status and Environmental Associations of the Rare Striated Darter, Etheostoma striatulum. By Andrew C. Abernathy and Hayden T. Mattingly Conservation Status of the Longhead Darter, Percina macrocephala, in Kinniconick Creek, Kentucky. By David A. Eisenhour, Audrey M. Richter and Joshua M. Shiering First Observation of a Natural Hybrid Between Endangered Roanoke Logperch (Percina rex) and Chainback Darter (Percina navisense). By James H. Roberts Minutes, Business Meeting, 36th Annual Meeting, Southeastern Fishes Council 2010 Treasurer's Report for the Southeastern Fishes Council
Keywords: fishes; population; environmental; conservation status; longhead darter; percina macrocephala; kinniconick creek; kentucky; hybrid; roanoke logperch; percina rex; chainback darter; percina navisense